If the sum of roots of the equation above for is of the form , find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Formula used :
cos ( 3 x ) = 4 cos 3 ( x ) − 3 cos ( x )
cos 2 ( x ) = 2 1 + cos ( 2 x )
cos ( 2 5 2 x ) cos ( 7 5 6 x ) − cos ( 5 0 4 x ) cos ( 1 5 1 2 x ) = 2
cos ( 2 5 2 x ) 4 cos 3 ( 2 5 2 x ) − 3 cos ( 2 5 2 x ) − cos ( 5 0 4 x ) 4 cos 3 ( 5 0 4 x ) − 3 cos ( 5 0 4 x ) = 2
4 cos 2 ( 2 5 2 x ) − 4 cos 2 ( 5 0 4 x ) − 3 + 3 = 2
− 4 cos 2 ( 5 0 4 x ) + 2 cos ( 5 0 4 x ) + 2 = 2
− 4 cos 2 ( 5 0 4 x ) + 2 cos ( 5 0 4 x ) = 0
cos ( 5 0 4 x ) = 0 or cos ( 5 0 4 x ) = 2 1
Observe patterns :
The sum of roots of cos ( 5 0 4 x ) = 0 for 0 < x < 2 π = 2 ( 5 0 4 ) = 1 0 0 8
The sum of roots of cos ( 5 0 4 x ) = 2 1 for 0 < x < 2 π = 2 ( 5 0 4 ) = 1 0 0 8
⇒ 1 0 0 8 + 1 0 0 8 = 2 0 1 6